Implementation of Islamic education to Improve Religious and Moral Aspects in Intan Cendekia Islamic Preschool - Suhadah, Suhadah (PeDaPAUD: Jurnal Pendidikan Dasar dan PAUD, 2022)
This study aims to determine the implementation of Islamic Education to improve aspects of religious and moral development, and what methods are used in the implementation of Islamic educationin Intan Cendekia Islamic Preschool. This research approach is a qualitative research with descriptive qualitative research which aims to explore and obtain accurate and objective data about the implementation of Islamic educationin Intan Cendekia Islamic Preschool. Qualitative data analysis is carried out interactively and takes place continuously at each stage of the research so that it is complete, and the data is saturated. Activities in data analysis, namely data reduction, data display, and conclusion drawing/verification. The results showed that the implementation of PAI in Intan Cendekia Islamic Preschool was quite good which was carried out through: (1) planning; (2) implementation; (3) evaluation. The method used in the implementation process is good. The methods chosen are the Play Method, Field Trip Method, Storytelling Method, Habituation Method, and Exemplary Method. In this way, the development of children's religious and moral values can develop properly.